Apologetika Di Era Revolusi Industri 4.0 - Fitriani, Kristiana (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
Christians are called not only to believe in the Lord Jesus and receive the gift of salvation, but are also called to account for their faith and belief to others, and even preach the gospel to everyone. In line with this call, apologetics becomes an effective means or tool to give an account of the Christian faith to everyone. Currently the world is entering an era known as the Industrial Revolution 4.0 era. This era brought significant changes to society. In this era, everything that is conventional begins to erode. This era will provide challenges as well as opportunities in the call of Christians to mission and apologetics. Seeing this phenomenon, it is necessary to formulate an apologetic model in relation to the 4.0 era. The purpose of this research is to produce an online Christian apologetics model that remains in accordance with Bible standards in the 4.0 era. This research was conducted using a qualitative approach with the type of phenomenological and theological research. Data collection was carried out using a literature study. This study resulted in the principles of online Christian apologetics in the 4.0 era which consisted of: apologetics actors, apologetics methods, and apologetics strategies.